Vitamin D may alleviate irritable bowel syndrome by modulating serotonin synthesis: a hypothesis based on recent literature - Yu, Xiao-Lan; Li, Cui-Ping; He, Lian-Ping (Frontiers in Physiology, 2023)
Numbers of studies found that serotonin play vital role in the development of depression and irritable bowel syndrome. Recent studies showed that vitamin D was associated in regulating the synthesis of serotonin. This review focus on the recent progress of the relationship between vitamin D and serotonin synthesis.